Seasonal changes in the essential oils of Aloysia oblanceolata Moldenke - Santos, Paulo Vinicius L.; Lima, Mateus Machado; Lucas, Flavia Cristina A.; da Silva, Joyce Kelly do R.; Maia, José Guilherme S.; Figueiredo, Pablo Luis B. (Frontiers in Chemistry, 2025)
IntroductionAromatic plant species that produce essential oils contain bioactive compounds and medicinal properties, and are thus used in traditional medicine. This study aims to analyze the seasonal variation in Aloysia oblanceolata Moldenke's essential oil's chemical composition in the Amazon region.MethodsThe botanical material was collected monthly over 1 year; the leaf essential oils were extracted by hydrodistillation, and their chemical composition was analyzed through gas chromatography–mass spectrometry (GC-MS). Local climatic parameters, such as insolation, temperature, relative humidity, and precipitation, were monitored. Multivariate statistical analyses were performed using hierarchical cluster analysis (HCA) and principal component analysis (PCA).Results and discussionThe AoEO yields ranged from 3.4% (December 2022 and February 2023) to 5.3% (August and September 2023), with an average of 4.3% ± 0.7%. Essential oil yields did not show a significant difference (p > 0.05) between the dry (4.7% ± 0.7%) and rainy (4.1% ± 0.6%) periods. GC and GC-MS identified 38 chemical constituents in the essential oils, comprising approximately 94.6%–97.1% of the oils analyzed in the seasonal variation study over the 12-month period. The chemical constituents that significantly correlated with climatic factors were trans-pinocamphone, β-pinene, and E-caryophyllene. Group I was statistically different from Groups II and III in terms of trans-pinocarvyl acetate content (I = 7.0 ± 0.5%; II = 9.1 ± 0.3%; III = 8.2 ± 0.6%). Group II differed from the other groups in terms of its β-pinene (I = 4.3 ± 0.5%; II = 5.2 ± 0.3%; III = 1.6 ± 0.9%), trans-pinocamphone (I = 13.1 ± 1.2%; II = 15.9 ± 0.4%; III = 12.5 ± 2.1%), and E-caryophyllene contents (I = 6.9 ± 0.7%; II = 4.7 ± 0.1%; III = 7.9 ± 1.6%). Furthermore, Group III differed from the other groups in terms of β-pinene content (I = 4.3 ± 0.5%; II = 5.2 ± 0.3%; III = 1.6 ± 0.9%). These results indicate seasonal variations in the chemical composition of the essential oils, possibly influenced by environmental factors and plant development.